2020
DOI: 10.3390/su12208597
|View full text |Cite
|
Sign up to set email alerts
|

Do Board Gender Diversity and Non-Executive Directors Affect CSR Reporting? Insight from Agency Theory Perspective

Abstract: Our paper provides a valuable contribution by exploring the following complex phenomenon: Do board gender diversity and reputational incentives of non-executive directors affect corporate social responsibility(CSR) reporting? To this end, we use panel data regression (fixed effect) to examine the above relationship by using data from the 2009 to 2019 timeperiod, by using data from non-financial firms listed on the Shanghai Stock Exchange. To deal with the possibility of an endogeneity problem, we have used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 100 publications
5
18
0
Order By: Relevance
“…Findings indicate that the coefficient of SI (β = 0.031, p < 0.05) in Model 1 is statistically significant and positive. These findings support H1 indicating that firms having gender diversity in boards are more likely to involve in CSR reporting and are in total alignment with studies (Hafsi and Turgut, 2013;Yasser et al, 2017;Guping et al, 2020) which also reported a positive association between firms' CSR reporting and BGD. These results imply that Chinese firms having female directors on boards are likely to disclose more CSR-related information because female directors compared to their male counterparts have different values and concerns regarding disclosure of social responsibility-related practices (Bear et al, 2010).…”
Section: Multivariate Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…Findings indicate that the coefficient of SI (β = 0.031, p < 0.05) in Model 1 is statistically significant and positive. These findings support H1 indicating that firms having gender diversity in boards are more likely to involve in CSR reporting and are in total alignment with studies (Hafsi and Turgut, 2013;Yasser et al, 2017;Guping et al, 2020) which also reported a positive association between firms' CSR reporting and BGD. These results imply that Chinese firms having female directors on boards are likely to disclose more CSR-related information because female directors compared to their male counterparts have different values and concerns regarding disclosure of social responsibility-related practices (Bear et al, 2010).…”
Section: Multivariate Analysissupporting
confidence: 84%
“…Besides, few studies have explored firms' CSR reporting behavior regarding BGD, and findings have been inconsistent across institutional contexts. For example, some studies evidenced a positive association between BGD and CSR reporting (Galbreath, 2011;Hafsi and Turgut, 2013;Harjoto et al, 2015;Yasser et al, 2017;Guping et al, 2020). In contrast, several studies reported a negative relationship (Zahra and Stanton, 1988;Molz, 1995), while others found no evidence in support of the BGD and CSR relationship (Coffey and Wang, 1998;Stanwick and Stanwick, 1998).…”
Section: Literature Review Theoretical Background and Hypotheses Csr Reporting And Bgdmentioning
confidence: 99%
See 1 more Smart Citation
“…160 studies analyse the role of female directors (e.g. Guping et al, 2020;Pucheta-Martinez and Gallego-Alvarez, 2019;Rao & Tilt, 2016a); 24 examine the presence of female managers (e.g. J.…”
Section: Type Of Female Involvement (Eg Board Of Directors Top Management Team Ceo and Relevant Committees)mentioning
confidence: 99%
“…Various researchers have argued about the direct association of CSR and ethical leadership [82][83][84]. To conclude, CSR as a business system can generate real returns for all stakeholders by implementing ethical values and sustainable work practices in an organization [85][86][87][88]. This notion of a socially responsible organization which works in the larger interest of society and the environment is transmitted to the corporate leaders and they, in turn, learn this ethical behavior on their part.…”
Section: Csr and Ethical Leadershipmentioning
confidence: 99%